Intervensi Konseling Kelompok Untuk Mengurangi Dampak Bullying Terhadap Kesehatan Mental Remaja - Catur Syalifah Salsabillah; Mochammad Aidhul Fitra; Muhammad Fikram Zaidan; Ati Kusmawati (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Bullying behavior is very vulnerable to occur in adolescent boys and girls. Depending on the context, bullying can occur in various places, ranging from educational or school environments, workplaces, homes, neighborhoods, playgrounds, and others. Bullying can have a significant impact on the mental health of adolescents, both victims and perpetrators. In victims, bullying can cause various problems, such as depression, anxiety, eating disorders, sleep disorders, suicidal thoughts, behavioral problems, substance abuse, aggressiveness, violence. This research uses the literature research method sourced from journals, articles, theses, from research that has been done before. This study aims to: (1) To find out the impact received by adolescent victims of bullying on their mental health. (2) To find out what methods are relevant to reduce the impact of bullying on adolescent mental health.